Experimental efficacy of vaccination of weaned piglets with a modified-live commercial PRRS virus vaccine against the challenge with a Spanish highly virulent PRRSV-1 strain - M. Cortey; M. Jiménez; L. Aguirre; J. M. Sánchez-Carvajal; J. Gómez-Laguna; I. Domingo-Carreño; H. Clilverd; M. Marcos; R. Menjon; S. Von Berg; E. Mateu (Porcine Health Management)
Abstract Background In 2020, a highly virulent PRRSV-1 strain emerged in Spain and rapidly spread across the country. The purpose of the present study was to test in a piglet model whether a commercial PRRSV-1 modified live vaccine was able to confer protection against strain R1, a representative of the emerging clade. For that purpose, two groups of 26 piglets were either vaccinated intradermally or kept as controls; 42 days later, half of the animals in each group were intranasally challenged with the R1 strain. Then, animals were followed to assess the development of clinical signs (until 14 days post-challenge), lung lesions (10- and 35-days post-challenge), weight gains, viremia and nasal shedding and the immune response (anti PRRS virus nucleoprotein antibodies) by ELISA and virus specific-interferon-γ secreting cells by ELISPOT). Results Challenge of naïve pigs resulted in high fever (up to 41.9 °C), lethargy and severely retarded growth (0.748 kg/day). In contrast, vaccinated/challenged pigs had less fever and for a shorter period, lower clinical scores and a higher average daily weight gain (0.940 kg/day), comparable to the unchallenged animals. At 10 days-post challenge, in naïve animals on average 49.1% of the lung was pneumonic (range 8–81%) while in vaccinated animals the average was 15.7% (4–41%). Duration of viremia was reduced in vaccinated animals and after 14 days post-challenge, most were negative by RT-qPCR. In contrast, 50% of the naïve/challenged pigs remained viremic at 35 days post-challenge. Vaccination induced rapid seroconversion and challenge of naïve animals resulted in 100% of ELISA-positive pigs by day 14 post-challenge. Regarding the development of IFN-γ responses, for vaccinated animals the frequencies increased until day 35 post-vaccination. After challenge, in vaccinated pigs, the peak of the R1-specific IFN-γ response was reached at 14 days and then the viremia ceased, although nasal shedding persisted in some vaccinated animals. Conclusions In the present trial, vaccination resulted in improved clinical course, better weight gain and reduced viremia. At the peak of the infection, lung lesions were reduced in most animals although some individuals still had extensive pneumonia. In summary, vaccination was shown to provide partial but significant protection against the highly virulent R1 strain.